Factors Affecting Accounting Information System Performance - Jihan Abigail; Elvis Ronald Sumanti; Ika Prayanthi (Universitas Islam Islam Sumatera Utara, 2022)
The objective of this study is to examine and find empirical evidence of factors that impacts Accounting Information System (AIS) performance among others user involvement in AIS development, technical capability of AIS personnel, size of organization, management support, formalization of AIS development, and user training and education program. The population used in this study are organizations listed in North Minahasa Regional Work Units in the year 2020. By means of purposive sampling method, this research had gathered primary data in the form of questionnaires from 60 respondents from 22 governmental organizations. The result from linear regression testing showed that only management support and formalization of AIS development had significant positive impacts on AIS performance. On the other hand, user involvement in system development, individual technical skills, size of organization, and user training and education were found to have no significant impacts on AIS performance.